Electron transfer reaction of Tris(1,10-phenanthroline) cobalt(III) complex [Co(phen)3]3+ and thiosulphate ion (S2O32−) in an aqueous acidic medium - R. Osunkwo, C; U. Nkole, I; D. Onu, A; O. Idris, S (International Journal of Advanced Chemistry, 2018)
The electron transfer reaction of Tris (1,10-phenanthroline)cobalt(III) complex by thiosulphate ion has been studied in an aqueous acidic medium. Stoichiometric determination shows that for one mole of the oxidant that was reduced, one mole of the reductant was consumed; the reaction conforms to an overall equation: 2[Co(phen)3]3+ + 2S2O32− → 2[Co(phen)3]2+ + S4O62− Kinetics study carried out under pseudo-first order condition shows that the reaction proceeded via a one-way acid-dependent pathway and was third order overall; zero order with respect to the oxidant concentration, second order with respect to the reductant concentration and first order with respect to the hydrogen ion concentration. The empirical rate law conforms to the equation: −   {Co(phen)3}3+] = a [H+] [S2O32−]2 ‘a’ = 128.26 dm6 mol−2 s−1: at [H+] = 2.0 × 10−2 mol dm−3, µ = 0.4 mol dm−3 (NaCl), T = 28 ± 1˚C and λmax = 495 nm.The rate of reaction increased at the increase in ionic strength and at the decrease in medium dielectric constant. Added cations and anions catalyzed and inhibited the reaction rates respectively. The Michaelis-Menten plot of 1/k1 versus 1/[S2O32−]2 started from the origin. Hence based on spectroscopic investigation, thermodynamic information from temperature dependence studies and kinetic evidence from Michaelis–Menten plots and the interactions with added ions, an outer-sphere mechanism has been rationalized for this reaction. The mechanistic scheme of the reaction was proposed via the stated mechanistic route.